Endometrial Stromal Nodule: A Rarity and a Pathological Challenge - Camilla Skovvang Borg; Peter Humaidan; Hanne Noer; Huda Galib Majeed (Case Reports in Obstetrics and Gynecology)
Endometrial stromal tumors are rare, and endometrial stromal nodule is the least common. In the region of Middle Jutland, Denmark, only two cases are reported since 1995. The nodules are benign; nevertheless, hysterectomy is the treatment of choice. Tumor margins are required for diagnosis and essential to differentiate it from an invasive stromal sarcoma whose prognosis is very different. We report a rare case of a 38-year-old woman, with presurgical diagnosis of a uterine tumor/polyp. She presented with nausea and changes in bleeding pattern and initially had a transcervical polyp resection performed. Histopathological examination showed the presence of an endometrial stromal tumor with unclear margins, and an invasive malignant endometrial sarcoma could not be excluded. Pathological examination revealed an endometrial stromal nodule with invasion, not exceeding three mm. Endometrial stromal tumors are interesting due to their rare existence and difficulties in establishing a histological diagnosis. Although endometrial stromal nodules are benign entities, they must be differentiated from the other invasive malignant stromal tumors, which may change the final prognosis. No preoperative diagnostic tools are at hand, and benign as well as malignant tumors are treated with hysterectomy.